Macronutrients Adequacy and Body Fat Percentage among Adolescent Football Athletes - Dittasari Putriana; Aurelia Nanda Astutiningrum; Kurnia Mar'atus Solichah (Universitas 'Aisyiyah Yogyakarta, 2025)
Excess body fat percentage in athlete can affect cardiovascular endurance, body composition, muscle endurance, muscle strength, and flexibility when they was performed. It also, when athletes with a low body fat percentage will have a higher risk of injury. Body fat percentage can be influenced by the adequacy level of macro nutrients (carbohydrates, proteins, fats). This study aimed to analyze the correlation between the adequacy level of macro nutrients and body fat percentage of adolescent football athletes at the PSS Development Center. This study was an observational analytical study with a cross-sectional study design. The sample of this study was 33 adolescent soccer athletes at the PSS Development Center who selected using a purposive sampling technique. The adequacy level of macro nutrient was obtained by a 1x24-hour recall interview method for 2 non-consecutive days. Body fat percentage was measured using a Bioelectrical Impedance Analysis (BIA) scale. Data analysis was performed using the Pearson Product Moment test with a p-value <0.05. The mean adequacy level of carbohydrate, protein, and fat were 70.26%±21.43; 79.66%±23.32 and 84.97%±24.56, respectively. The mean body fat percentage of adolescent athletes was 13.74%±3.61. This study found no correlation between the adequacy level of protein and fat intake with body fat percentage in adolescent football athletes (p=0.0781 and p=0.0783). However, a significant correlation was found between the adequacy level of carbohydrate and body fat percentage in adolescent football athletes (p=0.0042).